Penerapan Model Pembelajaran Inquiri untuk Meningkatkan Minat Belajar dan Pemahaman Konsep Matematika Siswa Kelas X SMKN 1 Dompu - Rini Kurniati; Masjudin Masjudin; Eliska Juliangkary (Lembaga Pusat Kegiatan Belajar Masyarakat (PKBM) Tunas Harapan, 2024)
This research aims to describe the application of the Inquiry Based Learning model which can increase interest and understanding of mathematical concepts in class X students at SMKN 1 Dompu. The type of research is classroom action research (PTK). This research was carried out in two cycles. Each cycle consists of four stages, namely planning, implementation, observation and reflection. The subjects in this research were 27 students. The research instruments used were interest questionnaires and test sheets. The results of research in cycle I showed that the students' learning Minar was in the Poor category with a percentage of 58.82% and students' conceptual understanding was in the Good Criteria with a completion percentage of 81.5%. Furthermore, in cycle II there was an increase in students' interest in learning to be in the Active category with a percentage of 64.78%, and students' understanding of concepts also increased to be in the Very Good Criteria by reaching a classical completion percentage of 90.92%. Thus, it can be concluded that through the application of the inquiry based learning model in mathematics learning, it can increase interest and understanding of concepts in class X students at SMK Negeri 1 Dompu. Keywords: inquiry based learning, interest in learning, understanding concepts